Investigating STEAP2 as a potential therapeutic target for the treatment of aggressive prostate cancer. - Jones, Leia A; Conway, Gillian E; Nguyen-Chi, Aimy; Burnell, Stephanie; Jenkins, Gareth J; Conlan, R. Steven; Doak, Shareen H (Cellular and Molecular Biology, 2023)
The expression of six transmembrane epithelial antigen of the prostate (STEAP2) is increased in prostate cancer when compared to normal tissue, suggesting a role for STEAP2 in disease progression. This study aimed to determine whether targeting STEAP2 with an anti-STEAP2 polyclonal antibody (pAb) or CRISPR/Cas9 knockout influenced aggressive prostate cancer traits. Gene expression analysis of the STEAP gene family was performed in a panel of prostate cancer cell lines; C4-2B, DU145, LNCaP and PC3. The highest increases in STEAP2 gene expression were observed in C4-2B and LNCaP cells (p<0.001 and p<0.0001 respectively) when compared to normal prostate epithelial PNT2 cells. These cell lines were treated with an anti-STEAP2 pAb and their viability assessed. CRISPR/Cas9 technology was used to knockout STEAP2 from C4-2B and LNCaP cells and viability, proliferation, migration and invasion assessed. When exposed to an anti-STEAP2 pAb, cell viability significantly decreased (p<0.05). When STEAP2 was knocked out, cell viability and proliferation was significantly decreased when compared to wild-type cells (p<0.001). The migratory and invasive potential of knockout cells were also decreased. These data suggest that STEAP2 has a functional role in driving aggressive prostate cancer traits and could provide a novel therapeutic target for the treatment of prostate cancer.